Reducing the number of pupils in French first-grade classes: Is there evidence of contemporaneous and carryover effects?. (2019) - Bressoux, Pascal; Lima, Laurent; Monseur, Christian
Highlights: By the end of Grade 1, small-class pupils' literacy scores were higher than the control pupils' scores. So, there is evidence for a positive contemporaneous effect for class size reduction. No evidence was found for Hawthorne effects. By the end of Grade 2, the advantage small class attendees had at Grade 1 was lost. So, no carryover effects were observed. Abstract: This study aims at investigating the contemporaneous and carryover effects of a class size reduction experiment. This experiment initially involved 100 reduced classes (average 10.5 pupils; range 8–12) that were contrasted with 100 full-size classes (average 21.3 pupils; range 15–27). Although the experiment was implemented only in Grade 1, the pupils have been followed up over a two-year period until the end of Grade 2. Multilevel growth curve modelling estimates show significant positive contemporaneous effect of the class size reduction in Grade 1, but no carryover effects during the following year. At the end of Grade 2, the effects have faded. Practical implications for a class-size reduction policy and limitations of the study are discussed.